Analisis Perkembangan Perkebunan Kelapa Sawit di Kabupaten Tanah Bumbu - Sudianti, Ni Ketut (PPJP ULM, 2018)
This research was conducted to know the productivity of oil palmplantation in Tanah Bumbu Regency and how the contribution of oil palmdevelopment to the regional income in Tanah Bumbu Regency. Data analysistechniques in this study using quantitative descriptive analysis techniques. Given theproductivity of oil palm plantations in Tanah Bumbu regency from the last five yearsexperienced an excellent development is evident from the results of oil palmplantation, productivity in 2016 reached 19,000 (Ton / Ha). The contribution of thepalm oil sector in 2016 to Rp 34.818.670.368 means that the commodity of palm oilcan boost economic growth and increase capital in Tanah Bumbu Regency.